Proposed guidelines for touristic management of micro-territories: the case of San Juan neighborhood, Oldtown, Quito - Ojeda Chiriboga, David Alexander (2024)
In this article, I review proposed guidelines for the touristic management of micro-territories, to establish the foundation for new neighborhood-oriented planning methodologies (micro-territories). I proposed an exploratory methodology upon which I built the baseline for organizing micro-territories considering three main axes. The first axis is a diagnosis, subdivided into components: tourism, social, and environmental, each with its indicators and evaluations. The information for its construction was gathered through direct observation and information compilation. The second axis corresponds to satellite localization and categorization of micro spaces. These were constructed on Google Earth, based on diagnostic information, and are integral parts of a micro-territory; The third axis consists of strategies for strengthening the micro-territory; in this section, I provide ideas to assist decision-makers in the studied neighborhood. The micro-territory of San Juan, located in Quito’s Oldtown was selected for this study. The results indicate that San Juan’s neighborhood has the potential to develop tourism activities, along with an important social base and good natural diversity. These aspects were reflected in four micro-spaces and the development of various strategies, ranging from public lighting to tree planting in the area. In conclusion, it is reaffirmed that the proposal is feasible; however, aspects such as its scope need to be adjusted, certain evaluation indicators need to be changed, or additional micro-spaces need to be included.